ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PROSES SELEKSI PENERIMAAN KARYAWAN DI RUMAH SAKIT UMUM DAERAH (RSUD) KAB. NGANJUK - Ika Novaliana (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2016)
This study aims to examine the factors - factors that potentially influence the decision of the selection process of recruitment in the General Hospital of kab. Nganjuk. The variables used in this study, is the level of education, gender (sex), age, physical state and attractiveness, expertise, and experience working as independent variables and the process of recruitment, selection decision as the dependent variable. Total sample used in this study were 81 samples of 430 population. In connection with the possibility of internal factors that occur in hospitals Nganjuk of 81 shared turned out a total of 61 were returned and can be processed. Data analysis technique used is multiple linear regression, validity and reliability, the classic assumption test and hypothesis testing using the F test and t test. Processing data using SPSS 16.0 software. The results of the study based on simultaneous test (F) turns F count (1,086) F ≤ critical (2.271989) meaning factors - factors including education level, gender (sex), age, physical state and attractiveness, expertise, and work experience simultaneously does not affect the decision process selection process for employees in hospitals Nganjuk. By using partial test (t), t (level of education: -0.882, gender: -0.988, age: 0,939, physical state and attractiveness: 0,482, expertise: 0.712, work experience: 1,104) ≤ t Critical (2,004) all not influential partially on the decision process selection process for employees in hospitals Nganjuk. And test the coefficient of determination (0.9%) shows that the factors - factors such as education level, gender (sex), age, physical state and attractiveness, skills, and work experience do not affect the decision of the selection recruitment process